Perbedaan Kapasitas Fungsional Paru Mahasiswa yang Latihan Aerobik Jump Rope dan Jogging - Raynaldo Marbun; Dewi Nur Fiana (Majority, 2022)
Students have dense activities so they often forget to do exercises that cause declining body health. Jump rope and jogging exercises which are types of aerobic exercise are practical exercises that can improve the functional performance of the body especially the functional capacity of the pulmonary. The purpose of this aerobic exercise research is to determine differences in the functional capacity of the pulmonary of students who did jogging and jump rope. RCT research with 35 students of the Faculty of Medicine, University of Lampung which was divided into a control group and an intervention group. The intervention group had a jogging exercise dose with requency 2 times a week, intensity 40%-90% Hearth Rate Reserve (HRR), time 30 minutes, aerobic type and jump rope exercise dose with frequency 4 times a week, intensity 70%-75% Maximum Hearth Rate (MHR), time 5 minutes, type aerobics. The mean VO2 Max value of the exercise group was higher than the control group and had significant differences. The mean VO2 Max jump rope group was higher than the jogging group but there was no significant difference between them. There was no significant difference between the jump rope and jogging exercise groups but there were significant differences between the exercise training groups and the control group so that jump rope and jogging exercises were considered to increase VO2 Max.